Patients' experiences of coping with multiple chronic conditions: A qualitative descriptive study. Issue 23 (3rd September 2019) - Cheng, Cheng; Bai, Jie; Yang, Cong‐Yan; Li, Ming; Inder, Kerry; Chan, Sally Wai‐Chi
Abstract: Objective: To explore the experiences of how Chinese adults cope with multiple chronic conditions in everyday life. Background: Having multiple chronic conditions is stressful, requiring people to make physical and mental adaptations. There is little evidence exploring how people cope with multiple chronic conditions, especially in an Asian context. Design: A qualitative descriptive design was employed. The Consolidated criteria for reporting qualitative research (COREQ) was used to report this study. Methods: This study was conducted in a tertiary referral and teaching hospital in Bengbu, Anhui, China, between August and October 2018. A purposive sample of 14 people with multiple chronic conditions, aged between 32 and 75 years, completed a demographic questionnaire and semi‐structured face‐to‐face interviews. The interviews were digitally recorded and transcribed verbatim. Qualitative content analysis guided data analysis. Results: Four distinctive themes comprising subthemes were developed from participants' narratives pertaining to coping with multiple chronic conditions: (a) appraising multiple chronic conditions, (b) addressing multiple chronic conditions management, (c) maintaining psychological well‐being and (d) fulfilling a social role. Illustrative quotations were cited to support each theme. Conclusions: This study underscores that people cope with multiple chronic conditions in everyday life by using a compendium of coping strategies. As one of the influencing factors, culture dominates the ways of coping at different levels among people with multiple chronic conditions. These findings expand the current literature on coping based on an Asian perspective and inform further cross‐culture research on this topic. Relevance to clinical practice: Healthcare professionals should understand peoples' experiences of coping with multiple chronic conditions to provide more holistic and dynamic health care to address their actual needs. Healthcare professionals should be acquainted with how culture impacts individuals' coping and develops culture‐tailored supportive programmes such as family‐based interventions, to promote the health of people with multiple chronic conditions.